Cardiac autonomic dysfunction and structural remodeling: the potential mechanism to mediate the relationship between obstructive sleep apnea and cardiac arrhythmias - Chen, Hao; Zhang, Qingfeng; Hao, Yueying; Zhang, Jingyi; He, Yang; Hu, Ke (Frontiers in Medicine, 2024)
Background: Cardiac arrhythmias are highly prevalent in patients with obstructive sleep apnea (OSA), especially atrial fibrillation (AF) and nonsustained ventricular tachycardia (NVST). Cardiac autonomic dysfunction and structural remodeling caused by OSA provide the milieu for cardiac arrhythmia development. This study aimed to determine whether OSA is associated with various cardiac arrhythmias and investigate potential pathophysiologic pathways between them.The analysis covered 600 patients with clinical suspicion of OSA hospitalized in Renmin Hospital of Wuhan University between January 2020 and May 2023. After undergoing sleep apnea monitor, all subjects received laboratory tests, Holter electrocardiography, and Echocardiography.Compared with those without OSA and adjusting for potential confounders, subjects with moderate OSA had three times the odds of AF (odds ratio [OR] 3.055; 95% confidence interval [CI], 1.002-9.316; P = 0.048). Subjects with severe OSA had three times the odds of AF (OR 3.881; 95% CI,; P = 0.015) and NSVT (OR 3.690; 95% CI, 0.809-16.036; P = 0.046). There were significant linear trends for the association between OSA severity with AF and NVST (P <0.05). And this association was mediated by cardiac structural changes including left atrial diameter, left ventricular diastolic diameter, right atrial diameter and right ventricular diameter. In addition, the ratio of low-frequency and high-frequency individually mediated the association between severe OSA and NVST.This study demonstrated that severe OSA was independently associated with AF and NSVT, and this association was mediated by autonomic nervous system changes and cardiac structural remodeling.